Abdominal examination. (February 2015) - Kara, Tonya; Evans, Helen M
<x xml:space="preserve">Abstract</x> The four short cases in the Clinical Examination give the candidate the opportunity to demonstrate the skills developed during basic training, including tailoring the clinical examination to difficult settings, such as a child of a difficult age, a bored child or a child who needs winning over quickly. The abdominal short case gives the candidate a chance to show their general approach to children and their families as much as their skill in detecting ascites.